Building microscopic soccer balls with evaporating colloidal fakir drops - Marín, Álvaro G. (National Academy of Sciences, 2012)
Evaporation-driven particle self-assembly can be used to generate three-dimensional microstructures. We present a unique method to create colloidal microstructures in which we can control the amount of particles and their packing fraction. To this end, we evaporate colloidal dispersion droplets on a special type of superhydrophobic microstructured surface, on which the droplet remains in Cassie–Baxter state during the entire evaporative process. The remainders of the droplet consist of a massive spherical cluster of the microspheres, with diameters ranging from a few tens up to several hundreds of microns. We present scaling arguments to show how the final particle packing fraction of these balls depends on the dynamics of the droplet evaporation, particle size, and number of particles in the system.